Perspektif Hukum Islam terhadap Dampak Alat Kontrasepsi bagi Keharmonisan Hubungan Suami Istri : Studi Kasus di Desa Sumberejo, Kec. Banyuputih, Kab. Situbondo - Siti Ayu Rahayu (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The use of contraceptives has become a common practice in society and is generally permitted under both Islamic law and positive law. Various types of contraceptives, including hormonal and non-hormonal as well as temporary and permanent methods, are widely used by married couples, including those in Sumberejo Village, Banyuputih District, Situbondo Regency. This study aims to analyze the impact of contraceptive use on marital harmony and to examine the Islamic legal perspective regarding these impacts. The research focuses on the negative effects of contraceptive use on marital harmony and the Islamic legal view concerning such effects. This study employed a mixed-methods approach using a concurrent embedded strategy, with qualitative research as the primary method supported by quantitative analysis. The findings indicate that hormonal contraceptives influence marital harmony through changes in physical appearance, marital intimacy, and the potential to have children. Statistical analysis revealed a significant effect of hormonal contraceptive use on marital harmony, as indicated by a calculated t-value of 3.868, which exceeded the critical t-value of 1.66023, with a significance value of 0.000 (< 0.05). From the perspective of Islamic law, the use of hormonal contraceptives is generally permissible provided that it does not contradict Islamic principles. If disputes arise due to their use, the concept of ishlah (reconciliation), as proposed by Imam Al-Shafi'i in Al-Umm, may serve as an appropriate solution to preserve marital harmony and family stability.